Sodium caseinate and OSA‐modified starch as carriers for the encapsulation of lutein using spray drying to improve its water solubility and stability. (21st July 2022) - Zhang, Bo; Yao, Yishun; Lu, Yifan; Xu, Yanfeng; Li, Wenhao; Yan, Wenjie
Summary: Lutein is a fat‐soluble substance with plentiful unsaturated carbon–carbon double bonds in the chemical structure. Spray‐drying formulations of lutein emulsions stabilised by a mixture of sodium caseinate (CS) and octenyl succinic anhydride‐modified starch (OS) yield lutein microcapsules. The yield (19.3–65.8%), encapsulation efficiency (74.7–82.9%), moisture (0.92–3.50%), wettability (226.8–392.4 s) and solubility (65.3–95.7%) were obtained in this study. The formulations with CS:OS (7:3) presented the excellent encapsulation efficiency (82.9%), glass transition temperatures (126.77 °C) and retention rate at 50 °C (80.51%), 25 °C (82.49%), and 4 °C (90.68%), and in UV light (75.44%) and lightness (80.40%) after 15 days. Based on the study, encapsulation would be an alternative for generating high value‐added products and could promote lutein's use as a functional ingredient with a 'clean label'. Abstract : Mechanism of lutein microcapsules formation.